The relationship between depression and lipid accumulation product: a population-based study - Zhu, Xianlin; Wang, Peng; Yue, Ya; Wu, Tiancheng; Cui, Jiali; Shu, Yanping; Ma, Ling (Frontiers in Psychiatry, 2024)
Background Lipid Accumulation Product (LAP) is a new type of obesity index. The relationship between LAP and depression is unclear, and this cross-sectional study was conducted to explore the relationship between LAP and depression using the National Health and Nutrition Examination Survey (NHANES) database from 2005–2018. Methods In our study, logistic regression analysis was used to calculate the odds ratio between depression and LAP, and subgroup analysis and sensitivity analysis were also performed to verify the robustness of the results. Results The analysis included 13,240 participants aged 20 years or older. After adjusting for multiple variables, LAP was positively associated with depression, OR 1. 50 (95% CI, 1. 05–2. 12). In subgroup analysis, LAP was significantly positively, associated with depression among male (2. 52, OR; 95% CI, 1. 39,4. 57), non-Hispanic Black (2. 55, OR; 95% CI, 1. 49,4. 36), those without diabetes (1. 67, OR; 95% CI, (1. 06,2. 61) or in the overweight (2. 09, OR; 95% CI, (1. 23,3. 54) subgroups. After inverse probability of treatment weighting (IPTW), the OR for the highest versus lowest quartile was 1. 55 (95% CI: 1. 24 – 1. 95). Conclusion There are positive results between LAP and depression after adjusting for multiple potential variables, and prospective studies are needed to verify the results.